X‐ray video defaecography is superior to magnetic resonance defaecography in the imaging of defaecation disorders. (17th February 2022) - Pääkkö, Eija; Mäkelä‐Kaikkonen, Johanna; Laukkanen, Hannele; Ohtonen, Pasi; Laitakari, Kirsi; Rautio, Tero; Oikarinen, Heljä
Abstract: Aim: The aim of this work was to study the technical success and diagnostic capability of magnetic resonance defaecography (MRD) compared with video defaecography (VD). Method: Sixty four women with defaecation disorders underwent both MRD and x‐ray VD over 1 year. The assessment by two radiologists in consensus was retrospective and blinded. The technical success of straining and evacuation was evaluated subjectively. The presence of enterocele, intussusception, rectocele and dyssynergic defaecation was analysed according to established criteria, with VD as the standard of reference. Results: It was found that 62/64 (96.9%) VD studies were technically fully diagnostic compared with 29/64 (45.3%) for MRD. The number of partially diagnostic studies was 1/64 (1.6%) for VD versus 21/64 (32.8%) for MRD, with 1/64 (1.6%) (VD) and 14/64 (21.9%) (MRD) being nondiagnostic. Thirty enteroceles were observed by VD compared with seven in MRD with moderate agreement ( κ = 0.41). Altogether 53 intussusceptions were observed by VD compared with 27 by MRD with poor agreement ( κ = −0.10 and κ = 0.02 in recto‐rectal and recto‐anal intussusception, respectively). Moderate agreement ( κ = 0.47) was observed in diagnosing rectocele, with 47 cases by VD and 29 by MRD. Dyssynergic defaecation was observed in three patients by VD and in 11 patients by MRD, with slight agreement ( κ = 0.14). Conclusion: The technical success and diagnostic capabilities of VD are better than those of MRD. VD remains the method of choice in the imaging of defaecation disorders.